2019
DOI: 10.3390/su11102978
|View full text |Cite
|
Sign up to set email alerts
|

Water-Saving Potential of Subsurface Drip Irrigation For Winter Wheat

Abstract: Groundwater plays a major role in agro-hydrological processes in the North China Plain (NCP). The NCP is facing a water deficit, due to a rapid decline in the water table because of the double cropping system. A two crop (maize and wheat) rotation is required to balance the food supply and demand, which leads to an imbalance between evapotranspiration (ET) and precipitation. Thus, there has been a decline of about 1.35 m yr−1 of groundwater (Luancheng Agroecosystem Experimental Station (LAES), NCP) during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Three irrigation treatments were surface drip irrigation (SDI), sub-surface drip irrigation (SSDI), and conventional irrigation (CI). SDI and SSDI were compared as previous studies reported an agronomic performance difference of various crops under both treatments (Martinez & Reca 2014;Umair et al 2019;Miyazaki & Arita 2020). Water in both SDI and SSDI treatment was released through drip line (emitter), and water in the CI treatment was applied through the open canal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three irrigation treatments were surface drip irrigation (SDI), sub-surface drip irrigation (SSDI), and conventional irrigation (CI). SDI and SSDI were compared as previous studies reported an agronomic performance difference of various crops under both treatments (Martinez & Reca 2014;Umair et al 2019;Miyazaki & Arita 2020). Water in both SDI and SSDI treatment was released through drip line (emitter), and water in the CI treatment was applied through the open canal.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, in Kediri, it can be known that the most positive agronomic performance was under the SSDI treatment. This may be attributed to an increase in water use efficiency due to less evaporation in the SSDI treatment than the other irrigation treatments (Hamada et al 2015;Umair et al 2019). Miyazaki and Arita (2020) observed that when the deeper the SSDI equipment is placed, the higher the root length and branching of sugarcane.…”
Section: Agronomic Performance Of Sugarcanementioning
confidence: 99%
“…The technical characteristics of SDI include small flow, local moistening, and frequent irrigation. When compared with surface irrigation methods, SDI has been found to have outstanding advantages, such as water conservation, lower amounts of required fertilizer, reducing evaporation losses, increasing crop WUE, irrigation WUE and crop yield, good adaptability to various terrain, uniform irrigation, and ease of technology integration [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the time-lag effect was more sensitive to SWC below a certain value. This may be attributed to the fact that the water stored at W4 could not meet the demand of winter wheat transpiration during the day (Umair et al, 2019), and the stoma was only partially opened, so the peak Tc was delayed (Kaufmann, 1982). Meanwhile, LT was poorly correlated to daily SWC at W1, W2 and W3, but highly correlated at W4, indicating that the soil moisture was a determinant for the hysteresis when soil moisture was below a threshold.…”
Section: Effect Of Meteorological Factors On Time-lag Effectmentioning
confidence: 99%